Surgical and Oncologic Outcomes With Intraoperative Radiation Therapy for Early Breast Cancer. Issue 4 (April 2023) - Friedman-Eldar, Orli; Layton, Christina; De Castro Silva, Iago; Moller, Mecker G; Allen, Ahkeel; Franceschi, Dido; Isrow, Derek; Samuels, Stuart; Takita, Cristiane; Avisar, Eli
Background: For selected patients with early-stage breast cancer (BC), intraoperative radiation therapy (IORT) has emerged as a convenient alternative to standard whole breast irradiation (WBI). We report a single institution experience with IORT in terms of oncologic outcomes, toxicities, and cosmesis. Methods: Clinicopathological and perioperative outcomes of patients who underwent IORT for early-stage BC at a public hospital from 2017 to 2020 were retrospectively retrieved. Toxicity was categorized to acute or chronic based on 6 months post-IORT cutoff. Results: 85 patients underwent IORT and had complete data, aged 49‐85 years (mean 62). Intraoperative radiation therapy added 23 minutes on average to the total operative time. Final stage was 0, I, and II in 40%, 58.9%, and 1.1% of patients, respectively. Mean tumor size was 0.8 cm (range .1-2.1), with ductal histology comprising 94% of cases. Surgical margins were positive in 2 patients, and adjuvant WBI was required in 5 patients. After a median follow‐up of 17 months (range 3-41), none of the patients had local recurrence and no mortality was recorded. Early wound complications included wound dehiscence (n = 1), seroma/hematoma (n = 15), and re-operation with loss of nipple-areola complex (n = 1). Chronic skin toxicities were reported in 10 (12%) patients and good or excellent cosmetic outcome was reported in 93% of patients. Conclusions: Utilizing IORT among low-risk early BC patients may be a safe and more convenient alternative to traditional WBI, with low toxicity rate, acceptable cosmetic results, and good oncologic outcomes at 17 months. Longer follow-up and further prospective controlled studies are needed to confirm these findings.